WIRELESS COMMUNICATION TECHNOLOGIES ENABLING RELIABLE INTERNET OF THINGS SMART FARMING APPLICATIONS - Wijaya, Hamid; Fujita, Miku; Nishida, Daiki (Journal of Computer Science Advancements, 2026)
The rapid expansion of smart farming systems has intensified the need for reliable wireless communication infrastructures capable of supporting Internet of Things (IoT) applications in heterogeneous agricultural environments. Ensuring stable connectivity in rural areas characterized by large coverage demands, energy constraints, and environmental interference remains a critical challenge. This study aims to evaluate wireless communication technologies and identify optimal configurations that enable reliable IoT-based smart farming operations. A mixed-method research design integrating large-scale field experiments and simulation-based scalability analysis was employed to assess LoRaWAN, NB-IoT, Zigbee, Wi-Fi, and 5G IoT modules. Reliability was measured using packet delivery ratio, latency, coverage range, scalability, and energy consumption indicators. Results indicate that no single technology achieves optimal performance across all reliability dimensions. LPWAN technologies demonstrated superior energy efficiency and wide-area coverage, while 5G achieved the lowest latency and highest throughput. Hybrid communication architectures consistently outperformed single-technology deployments, improving packet delivery ratio and operational resilience under varying environmental conditions. The study concludes that context-aware integration of complementary wireless technologies provides the most reliable and sustainable solution for smart farming IoT ecosystems.